2011
DOI: 10.1186/1743-7075-8-64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a conventional energy-restricted modified diet with or without meal replacement on weight loss and cardiometabolic risk profile in overweight women

Abstract: BackgroundAbdominal obesity, atherogenic dyslipidemia and hypertension are essential risk factors for cardiovascular diseases. Several studies showed favorable effects of weight loss in overweight subjects on cardiometabolic risk profile.MethodsThis open-label, randomized, controlled study investigated the effect of an energy-restricted modified diet with (MR) or without meal replacements for weight control (C) on weight loss, body composition and cardiometabolic risk profile in overweight women. Of 105 random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 28 publications
(34 reference statements)
3
39
1
Order By: Relevance
“…After eight weeks of intervention, mean weight loss in both groups (6.5 ± 3.5 kg in HC group and 6.8 ± 3.6 kg in HP group) were similar to other studies done previously (5.9-7.4 kg) which lasted twelve weeks [10,12,29]. A modest weight loss up to 5% has been shown to reduce the risk of developing obesity associated diseases [30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…After eight weeks of intervention, mean weight loss in both groups (6.5 ± 3.5 kg in HC group and 6.8 ± 3.6 kg in HP group) were similar to other studies done previously (5.9-7.4 kg) which lasted twelve weeks [10,12,29]. A modest weight loss up to 5% has been shown to reduce the risk of developing obesity associated diseases [30].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have demonstrated that weight loss and weight maintenance was greater in the meal replacement groups compared to the conventional energy restricted diets while the calorie goal for the groups was equivalent [8][9][10]. Meal replacements coupled with low-calorie diet considerably increase the number of responders [11,12] and provide an effective option for weight reduction in overweight and obese subjects [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable with previous exercise studies where fat mass decreased and lean mass remained unchanged or increased (19, 25, 26). In contrast, studies that use energy restriction and exercise for weight loss often observe reductions in lean mass that typically accounts for 22‐30% of weight loss (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…A dietary approach for reducing MetS risk emphasises nutrient density, entailing limited consumption of whole grains and saturated and trans fats, increased consumption of a variety of fruit and vegetables, and the novel concept of discretionary calories [8]. Weight loss can be achieved by a conventional, structured, energy-restricted, modified diet-with or without meal replacement [9]. In addition, insulin sensitivity is affected by the quality and quantity of dietary fats, which independently affect body weight (BW).…”
Section: Introductionmentioning
confidence: 99%